Dexmedetomidine as an Adjunct to Anti-Hypertensive Medication in Hemodynamic Management of Post-Operative Young Patients with Pre-Eclampsia - Nadeem, Muhammad Faisal; Haq, Ihtisham Ul; Asghar, Muhammad; Jelani, Farhat Afshan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare hemodynamic stability and patient outcomes when using dexmedetomidine as an adjunct to anti-hypertensive medication in post-operative young patients with pre-eclampsia Study Design: Quasi-experimental study Place and Duration of Study: Department of Anesthesia, Combined Military Hospital Bannu, Pakistan from 15 Jan - 15 Dec 2023. Methodology: A total of 180 patients were recruited for this quasi-experimental study. Patients were divided into Group-D (n=80) to receive Dexmedetomidine along with standard anti-hypertensive therapy, which included intravenous Labetalol, and Group-S (n=80) to receive standard anti-hypertensive therapy with intravenous Labetalol alone. Primary variables studied were hemodynamic profile in all patients, including heart rate and blood pressure checked at 1,3,6,12,18, and 24 hours. Secondary variables studied were sedation levels, mean total dose of analgesia required for post-operative pain in 24 hours, and the incidence of adverse effects including bradycardia, hypotension, nausea/vomiting and headache. Results: Mean arterial pressure (MAP) after 01 hour of therapy between Group-D and Group-S was 98.64±1.63 mmHg versus 100.55±4.75 mmHg (p=0.001), after 03 hours of therapy was 85.56±1.27 mmHg versus 89.13±2.29 mmHg (p<0.001), after 06 hours of therapy was 77.56±1.36 versus 89.35±2.90 mmHg (p<0.001), after 12 hours of therapy was 74.33±1.38 mmHg versus 82.94±4.26 mmHg (p<0.001), after 18 hours of therapy was 70.46±0.82 mmHg versus 78.61±0.60 mmHg (p<0.001) and after 24 hours of therapy was 67.99±1.08 mmHg versus 78.64±0.57 mmHg (p <0.001). Conclusion: Addition of Dexmedetomidine to standard anti-hypertensive therapy results in a better hemodynamic profile, better patient comfort, less requirement for analgesia with a tolerable adverse effects profile.